4CPS-197 Determining the necessary components of a pharmaceutical care complexity screening tool: an E-delphi study. (March 2019) - Alshakrah, M; Steinke, D; Tully, M; Williams, S; Lewis, P
Abstract : Background: With increased pressure on clinical pharmacy services there is a demand for reliable screening tools to appropriately allocate pharmaceutical care to those patients with most urgent and/or complex needs. Several such tools have been developed, however, they are often locally developed with a lack of agreement on their components. To date, no broad consensual agreement of experts exists on valid components of a pharmaceutical care complexity screening tool in the adult hospital setting. Purpose: To obtain consensus on the necessary components of a pharmaceutical care complexity screening tool for use on admission to hospital. Material and methods: Complexity tool components were identified and refined in three phases: first, a systematic literature review was conducted to identify existing tools and their components. Second, a national survey and semi-structured telephone interviews identified non-published tools and their components. The obtained components from phase I and II were reviewed by the research team and an expert reference group to remove non-clinical factors and duplicates. Third, an expert Delphi panel, including international leading pharmacists, researchers and clinicians, was recruited by email to take part in a two-round Delphi study. Items were scored. The panel were asked to rank each component according to importance via a web-based anonymised electronic questionnaire using a nine-point Likert-scale. Consensus was set at 67%: items that 67% of people deemed to be important were listed. Ethical approval was not required. Results: Forty-one invited experts joined the panel and completed round one, and 33 of them completed the second round. One-hundred and nine of the complexity tool components were initially identified and validated by the panel. After two Delphi rounds, 92 components (84.4%) achieved the limit of agreement for importance. These were grouped into three component types (demographic, clinical-related and medication-related) and reduced to 31 items for inclusion into a screening tool. Conclusion: This study systematically and rigorously identified a set of 31 items which are important for assessing pharmaceutical complexity. This information can then be used for the development and refinement of future and current pharmaceutical complexity screening tools that can aid more efficient targeting of hospital clinical pharmacy services. References and/or acknowledgements: No conflict of interest.